2014
DOI: 10.1007/s00167-014-3315-8
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and intra-observer agreement of femoroacetabular impingement (FAI) parameters comparing plain radiographs and advanced, 3D computed tomographic (CT)-generated hip models in a surgical patient cohort

Abstract: III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 21 publications
0
22
0
Order By: Relevance
“… 15 , 23 Although originally measured on MRI, a previous study showed little benefit over plain radiographs in improving inter-observer agreement in cam-type FAI morphology. 59 Nevertheless, it remains an important measure of cam-type FAI as adequate correction has been correlated with positive outcome following FAI surgery. 60 …”
Section: Discussionmentioning
confidence: 99%
“… 15 , 23 Although originally measured on MRI, a previous study showed little benefit over plain radiographs in improving inter-observer agreement in cam-type FAI morphology. 59 Nevertheless, it remains an important measure of cam-type FAI as adequate correction has been correlated with positive outcome following FAI surgery. 60 …”
Section: Discussionmentioning
confidence: 99%
“…Strengths of this study include its prospective study design, large sample size relative to previously published studies and inclusion of a wide variety of hip pathologies [ 6 , 7 ]. However, we acknowledge the following limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Although measurement of the LCEA was initially established and validated using standard anteroposterior pelvic (AP) radiography, recent trends have favored its measurement on computed tomography (CT) [ 6–8 ]. The increasing popularity of CT is, in part, attributed to its improved accuracy for visualization of bony morphology and preoperative planning relative to other imaging modalities in patients undergoing hip surgery [ 7 , 9–11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Greater alpha angles are associated with athletic‐related groin pain, chondral defects, and cam decompression . The most common threshold is 55° . The beta angle of Beaule is clinically used to determine posterior impingement, which is an indication for surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Acetabular dysplasia (AD) affects both sides of the joint and refers specifically to an acetabulum that is either shallow or underdeveloped. Previous studies have compared radiographic and CT imaging for select parameters of FAI and AD but have not comprehensively investigated the intermodality, interrater, and intrarater consistencies of lateral center edge, Tonnis, alpha, and beta angles in prearthritic hips. The primary objective of this study was to determine whether radiographs with an AP pelvis view and 45° Dunn lateral view reliably correlate with CT in the context of lateral center edge, Tonnis, alpha, and beta angle measurements for the diagnosis of FAI or AD.…”
Section: Introductionmentioning
confidence: 99%